ZASADA PAŃSTWA SPRAWIEDLIWOŚCI SPOŁECZNEJ JAKO ZASADA PUBLICZNEGO PRAWA GOSPODARCZEGO - Strzyczkowski, Kazimierz (Wydział Prawa i Administracji UAM, 2007)
In the paper, the author postulates that the principle of a social justice state should be added to the catalogue o f public economic law and presents arguments which support that proposal. Further he claims that this principle, the nature of which pertains to the political system of the state, orientates the whole process of the state influencing the economy, and constitutes the state’s objective, i.e. the state’s intervention in the economy in a situation when the fundamental values, including social justice, are at risk. This principle is addressed to organs of public administration as well as the legislative and judiciary organs of the state, which carry out the directives which, depending on the functions they perform, arise for them from the principle o f a social justice state, taking into account other principles, such as the principle of a democratic state of law, of subsidiarity, proportionality and economic rights and freedoms. Implementation of the principle of a social justice state is realised in a number of ways and through different means engaged to achieve integration of the organs of public authorities into the economy, as well as through the states direct economic activity, having regard to the limitations arising from the constitutionally protected individual rights and liberties.
THE PRINCIPLE OF A SOCIAL JUSTICE STATE AS A PRINCIPLE OF PUBLIC ECONOMIC LAW